SPSS - NorusÃåis, M. J. (Marija J.) 1948-.; SPSS Inc. (Chicago SPSS Inc., 1991)
A student version of the SPSS/PC+ system. Contains the tools for preparing the statistical analyses most frequently encountered in both classroom and professional environments. Allows students to store and analyze up to fifty variables and an unlimited number of cases.
Title from disk label.
Text by Marija J. NorusÃåis.
Issued also on 3 1/2 in. computer disk.
System requirements: IBM PC/XT, PC/AT, PS/2, or compatibles (including 386-based machines); at least 512K RAM; PC- or MS-DOS 3.0 or higher; 10MB (minimum) hard disk.
Keywords: Social sciences -- Statistical methods -- Software